Analysis of the Effect of AFAD Management Cycle on Reducing Risks by Adapting to Earthquake with ANP Method and Interpretation of its Effect on Health and Safety - Aksüt, Güler (Fırat University, 2025)
Türkiye is located between the Eurasian plate in the north and the Arabian and African plates in the south, which move northwest and north. Many earthquakes caused by active intraplate faults occur in our country. Earthquakes that can cause damage and loss of life are those with magnitudes five and greater. This study was carried out with the aim of not preventing earthquakes, which are the most harmful and disastrous natural events among natural disasters, but to be effective in ensuring the health and safety of employees and other parts of society by taking a proactive approach. ANP method was used in the study. The interconnected activities of reduction, preparation, intervention and recovery in the disaster management cycle were determined as criteria and the relationships between these criteria and the sub-criteria were taken into account and their importance weights were determined in line with expert opinions. Risk assessment had the highest weight of 0.186417. The study will contribute to reducing or preventing the effects of health, security, social, economic and environmental losses and damage caused by the earthquake by determining the priorities in the implementation of the disaster management plan.

Türkiye, kuzeyde Avrasya levhası ile güneyde kuzeybatı ve kuzeye hareket eden Arabistan ve Afrika levhaları arasında yer almaktadır. Ülkemizde levha içi aktif fayların sebep olduğu çok sayıda deprem meydana gelmektedir. Hasara ve can kayıplarına neden olabilen depremlerin büyüklükleri ise beş ve daha büyük olanlardır. Yapılan bu çalışma da doğal afetler arasında en zararlı ve felaketli doğa olayı olan depremlerin önlenmesine engel olunmasa da proaktif yaklaşım sergileyerek çalışanların ve toplumun diğer kesiminin sağlık ve güvenliklerini sağlamada etkili olması amacıyla yapılmıştır. Çalışmada ANP yöntemi kullanılmıştır. Afet yönetim döngüsünde yer alan azaltma, hazırlık, müdahale ve iyileştirmeden oluşan birbirine bağlı faaliyetleri kriter olarak belirlenerek bu kriterlerin birbiri ve alt kriterler içerisindeki ilişkileri dikkate alınarak uzman görüşleri doğrultusunda önem ağırlıkları belirlenmiştir. En yüksek ağırlığı 0,186417 ile risk değerlendirme oluşturmuştur. Yapılan çalışma afet yönetim planının uygulanmasında önceliklerin belirlenmesiyle depremin neden olduğu sağlık, güvenlik, sosyal, ekonomik ve çevresel kayıp ve zararların etkilerini azaltmaya veya önlemeye katkı sağlayacaktır.
AFAD Yönetim Döngüsünün Depreme Uyarlanarak Riskleri Azaltmadaki Etkisinin ANP Yöntemi ile Analizinin Yapılması, Sağlık ve Güvenliğe Etkisinin Yorumlanması
Keywords: Geological Sciences and Engineering (Other); Yer Bilimleri ve Jeoloji Mühendisliği (Diğer)